KEKELIRUAN PELAFALAN FONEM DALAM KOSAKATA BAHASA INDONESIA OLEH VLOGGER ASING BERBAHASA INDONESIA - Rima Rismaya; Sugeng Riyanto (Kajian Linguistik dan Sastra, 2021)
This research was conducted to describe the phonemic pronunciation errors which include vocals and consonants, and consonant accompaniment sounds in Indonesian vocabulary conducted by Indonesian-speaking foreign vloggers. This research is a descriptive qualitative research with data collection method using refer and note method with tapping technique. The data source of this research is the speech of two BIPA speakers from Korea namely Akang Daniel and Hari Jisun and two BIPA speakers from Russia namely Irina WS and Kseniia and Josef on their respective Youtube channels. Analysis of research data using the referential equivalent method with the determinant element technique. Presentation of data uses phonetic symbols based on The International Phonetic Alphabet or IPA. The results showed that the phonemic pronunciation error in the Indonesian vocabulary by Indonesian-speaking foreign vloggers occurred at the vowel and consonant levels. Vocal pronunciation errors include phonemes /a/, /e/, /i/, /ə/, /ε/, and /u/, while consonant pronunciation errors include phonemes /r/, /s/, /d/, /k/, /h/, /t/, /y/, /x/, and /ŋ/. There are four sounds accompanying the mistake of consonant pronunciation, namely gemination, vocalization, aspiration, and glottalization.